2009
DOI: 10.1007/s00026-009-0005-1
|View full text |Cite
|
Sign up to set email alerts
|

Left and Right Length of Paths in Binary Trees or on a Question of Knuth

Abstract: We consider extended binary trees and study the joint right and left depth of leaf j, where the leaves are labelled from left to right by 0, 1,..., n, and the joint right and left external pathlength of binary trees of size n. Under the random tree model, i.e., the Catalan model, we characterize the joint limiting distribution of the suitably scaled left depth and the difference between the right and the left depth of leaf j in a random size-n binary tree when j ∼ ρn with 0 < ρ < 1, as well as the joint limiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Motivated by the results of Bousquet-Mélou [3], and Panholzer [15] for naturally embedded binary trees, and the results of Schaeffer and Jacquard [9], and Del Lungo, Del Ristoro and Penaud [6] for a subclass of ternary trees, we embedd ternary trees in the plane in the following way. The root node has position zero.…”
Section: The Embedding Of Ternary Treesmentioning
confidence: 99%
See 3 more Smart Citations
“…Motivated by the results of Bousquet-Mélou [3], and Panholzer [15] for naturally embedded binary trees, and the results of Schaeffer and Jacquard [9], and Del Lungo, Del Ristoro and Penaud [6] for a subclass of ternary trees, we embedd ternary trees in the plane in the following way. The root node has position zero.…”
Section: The Embedding Of Ternary Treesmentioning
confidence: 99%
“…The study of tree families embedded in the plane has recently received a lot of attention. Binary trees, complete binary trees, more generally simply generated tree families, and several different families of planar trees have been considered in a series of papers [4,5,13,8,3,2,11,12,7,15]. It has been shown that embedded trees are closely related to a random measure called ISE (Integrated SuperBrownian Excursion).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several families of embedded trees have been studied in the literature. Binary trees, complete binary trees, several different families of planar trees and more generally simply generated tree families have been considered in a series of papers [8,9,20,13,3,2,17,18,12,22,14]: it has been showed that embedded trees naturally arise in the context of map enumeration and that properties of embedded trees are closely related to a random measure called Integrated Superbrownian Excursion. Combinatorial properties of embedded ternary trees where studied using bijections between embedded ternary trees and non-separable rooted planar maps [16,10], where the authors studied a particular subclass of embedded ternary trees named skew ternary trees [16], or left ternary trees [10], which are embedded ternary trees with no node having label greater than zero.…”
Section: Introductionmentioning
confidence: 99%